Press Freedom in the Digital Era from the Perspective of Journalistic Ethics - Afif Muthoharoh; Maziyyatul Muslimah, (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2026)
This study aims to analyze how press freedom is exercised within the framework of journalistic ethics in the digital age in Indonesia. The rapid development of digital media has transformed news production and distribution, creating new challenges for implementing ethical principles. Pressures from platform algorithms, market competition, and the demand for online popularity often encourage media outlets to prioritize speed and attractiveness over accuracy and verification, raising concerns about responsible press freedom. This study employs a qualitative descriptive method with a literature review approach. Data were collected from various sources, including press laws and regulations, journalistic codes of ethics, academic literature, previous research, and digital media reports. The data were analyzed to examine the relationship between press freedom, ethical responsibility, and digital journalistic practices. The findings reveal that press freedom in Indonesia faces significant challenges in maintaining professionalism and moral responsibility amid the rapid flow of digital information. Many media outlets tend to emphasize publication speed and news appeal to gain audience attention, thereby potentially neglecting verification and information accuracy. Nevertheless, a number of media outlets and journalists continue to strive to maintain ethical standards by strengthening editorial guidelines, improving media literacy, and collaborating with supervisory institutions such as the Press Council. These findings indicate that the sustainability of press freedom in the digital age is highly dependent on the commitment of media outlets and journalists to uphold journalistic ethics, as well as on strengthening institutional oversight and increasing public awareness of media literacy.